DETERMINING THE COEFFICIENT OF RESTITUTION DURING THE IMPACT OF BODIES: TESTING THE NEWTON HYPOTHESIS - Zdeshchyts, V.; Zdeshchyts, A. (Physical and Mathematical Education, 2021)
The methodology for conducting laboratory work in physics has been developed, which uses a smartphone as a measuring complex to determine the coefficient of restitution (COR) when a ball falls on the surface of the plate. Newton's hypothesis regarding the independence of the coefficient from the velocity was tested.Formulation of the problem. During a pandemic, when the movement of students is limited, it becomes impossible to perform face-to-face laboratory work in physics. Therefore, it is extremely important to provide students with methodological and instrumental support for conducting laboratory work remotely.Materials and methods. The problem was solved with the developed miniature mobile research installations in the BYOD technology style. Methodologically, the work was based on the known laws of mechanics. The main scientific and practical results were obtained using the registration of sound by a smartphone during a collision of a ball with a plate, video registration of the trajectory of movement with a smartphone in slow motion mode, oscillation of the duration of the impact. Results. The main result of the work is the development of a miniature research installation and methods of its use for remote laboratory work "Determination of the coefficient of restitution of velocity during the impact of bodies". It is proved that Newton's hypothesis regarding the independence of the COR from the speed of the ball falling on the plate is refuted. At speeds less than 0.5 m/s, the coefficient of restitution increases.Conclusions. The method of video recording in the mode of "slow motion" allows to use a smartphone to track the dependence of the COR on the speed for balls made of different materials: glass, steel, polybutadiene, plastic to the value . The most stable results can be obtained by the sound method if use tennis balls with a diameter of 40 mm. Comparison of the sound method with simultaneous video recording of a tennis ball falling on a steel plate proved that the results are consistent and both methods give the same value of the COR: . There is a constant excess of height by the sound method by 1-3 mm from the actual, and heights less than 15-20 mm are not registered.
Keywords: the coefficient of restitution; Newton's hypothesis; BYOD technology; smartphone; mobile applications